Water security threats and challenges following the rupture of large tailings dams - Pacheco, Fernando António Leal; de Oliveira, Mariângela Dutra; Oliveira, Marina Santos; Libânio, Marcelo; do Valle Junior, Renato Farias; de Melo Silva, Maytê Maria Abreu Pires; Pissarra, Teresa Cristina Tarlé [UNESP]; de Melo, Marília Carvalho; Valera, Carlos Alberto; Fernandes, Luís Filipe Sanches (Elsevier, 2022)
The rupture of mine-tailings dams can severely contaminate rivers, because released tailings can interact with water for years keeping contaminant concentrations high. The general purpose of this study was to examine the rupture of B1 tailings dam in Ferro-Carvão stream (municipality of Brumadinho, state of Minas Gerais, Brazil), which occurred in 25 January 2019 and contaminated the main water course (Paraopeba River) with 2.8 Mm3 of metal-rich tailings. The specific purpose was to assess the percentage of non-conforming concentrations following the event, considering the Normative Deliberation COPAM/CERH-MG no. 1. The results showed non-conforming aluminum, iron, manganese, lead, phosphorus and turbidity concentrations, clearly above pre-rupture averages, especially in the rainy period. The catastrophe triggered the suspension of Paraopeba River as drinking water source to the Metropolitan Region of Belo Horizonte (BHMR; 6 million people). Since then, the supply to the BHMR became an everyday challenge to water management authorities, because the Paraopeba source represented a 30% share. Mitigation measures are therefore urgently needed. As complementary objective to this study, we aimed to verify the possibility to restore drinking water supply through conventional treatment. The treatability of Paraopeba River water was assessed by the Raw Water Quality Index considering the rainy and dry periods in separate. The results suggested the possibility to lift up the suspension in the dry period, improving the regional water security. Considering the huge dataset on which this study is standing, our results are generalizable to similar events with sparser information.
Keywords: Non-conforming concentrations; Paraopeba River; Seasonality; Tailings dam rupture; Water security; Water treatability